Sigmoid Volvulus Complicating Postpartum Period - Kelsey E. Ward; Erin Blake; Eduardo Gonzalez; Frederic Pieracci; Meredith Alston (Case Reports in Obstetrics and Gynecology)
Background. Sigmoid volvulus is a rare complication of pregnancy and the puerperium. Case. A 19-year-old patient, gravida 1 para 0 at 41 0/7 weeks of gestation, admitted for late-term induction of labor underwent an uncomplicated primary low transverse cesarean delivery for arrest of descent. Her postoperative period was complicated by sudden onset of abdominal pain and the ultimate diagnosis of sigmoid volvulus. Conclusion. Prompt surgical evaluation of an acute abdomen in the postpartum period is essential; delayed diagnosis and treatment can lead to significant maternal morbidity and mortality.